Cardiac Involvement in COVID-19 Patients: A Contemporary Review - Domenico Maria Carretta; Aline Maria Silva; Donato D'Agostino; Skender Topi; Roberto Lovero; Ioannis Alexandros Charitos; Angelika Elzbieta Wegierska; Monica Montagnani; Luigi Santacroce (MDPI AG, 2021)
Background: The widely variable clinical manifestations of SARS-CoV2 disease (COVID-19) range from asymptomatic infections to multiple organ failure and death. Among the organs affected is the heart. This does not only affect people who already have previous cardiovascular problems, but also healthy people. This is a reason not to overlook any symptoms or to perform targeted examinations, even if apparently unrelated to the heart, for quick recognition and timely therapy. Aim of the study: This review recapitulates the current state of knowledge on the potential mechanisms and manifestation of myocarditis in patients with COVID-19 infection. Methods: A web-based search of published data was performed for all relevant studies on patients diagnosed with a COVID-19-induced acute myocarditis, and a total of 50 reports were included. The analysis of the studies evaluated highlights a male predominance, with the average age of patients being 55 years. The most common presenting symptoms included fever, shortness of breath, cough, and chest pain. Among ECG changes, non-specific ST-segment and T-wave amplitude alterations and ventricular tachycardia episodes were reported. Finally, we wanted to use a general evaluation without distinguishing between various countries, taking into consideration only the peer or reviewer, regardless of the declared value of the journals that have been published. Results and critical findings: The most common presenting symptoms included fever, shortness of breath, cough, and chest pain. Among ECG changes, non-specific ST-segment and T-wave amplitude alterations and ventricular tachycardia episodes were reported. In most patients, elevated levels of cardiac and inflammatory biomarkers were measured. Left ventricular dysfunction and hypokinesis were commonly exhibited symptoms. Cardiac Magnetic Resonance Imaging (CMRI) confirmed the diagnosis of myocarditis with features of cardiac edema and cardiac injury. Nine patients underwent histopathological examination. Treatment with corticosteroids and immunoglobulins was the most applied strategy following the administration of antivirals. Discussion: Despite the exponentially growing knowledge on the management of COVID-19 infection, current available data on SARS-CoV2-correlated myocarditis are still limited, and several difficulties may be encountered in the differential diagnosis of acute myocarditis in the context of COVID-19 disease. Conclusions: While diagnostic criteria and evaluation strategies for myocarditis are well described, no guidelines for the diagnosis and treatment of myocarditis in COVID-19 patients have yet been established. Therefore, further research is needed to advance the understanding of this disease process and define the most appropriate strategic approach in these patients.